2013
DOI: 10.1080/03075079.2013.823933
|View full text |Cite
|
Sign up to set email alerts
|

The challenges and prospects of access to higher education at UNISA

Abstract: This article debates access and success at the University of South Africa (UNISA).UNISA is an open distance learning (ODL) institution that provides higher education opportunities to working adults who would otherwise not have the opportunity to acquire a higher education qualification at full-time contact institutions. The article sketches the challenges and prospects of ODL. It teases out the challenges of ODL articulation, learner support, recognition of prior learning, and poor throughput rate. Substantive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 18 publications
1
28
1
Order By: Relevance
“…Moreover a tutor further specified that for physically challenged learners, access to the institution seemed easier because the ramps to assist with their movement are there in all the corridors. The above findings confirm what literature state 5,7,8 regarding access and inclusiveness of all people within the ODL context. On the other hand, for learners with visual impairment, the findings have shown that they got support from both lecturers and other learners, which upholds what 5 pointed out regarding the necessity of supporting and caring for learners in the ODL environment as opposed to those enrolled for traditional face to face instruction.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover a tutor further specified that for physically challenged learners, access to the institution seemed easier because the ramps to assist with their movement are there in all the corridors. The above findings confirm what literature state 5,7,8 regarding access and inclusiveness of all people within the ODL context. On the other hand, for learners with visual impairment, the findings have shown that they got support from both lecturers and other learners, which upholds what 5 pointed out regarding the necessity of supporting and caring for learners in the ODL environment as opposed to those enrolled for traditional face to face instruction.…”
Section: Discussionsupporting
confidence: 91%
“…Similar issues are reported across Africa (Boitshwarelo, 2009;Breetzke, 2007;Mtebe & Raisamo, 2014;Rye & Stokken, 2012;Wright, Dhanarajan, & Reju, 2009). The growing divide between rural and urban areas (Gulati, 2008;Nyerere, Gravenir, & Mse, 2012;Oladokun & Aina, 2011) and the cost and inconvenience of having to use internet cafes is also documented (Andersson & Gronlund, 2009;Letseka & Pitsoe, 2014;Rye & Stokken, 2012) and reflected in the views of Eritrean students based in rural areas.…”
Section: Discussionmentioning
confidence: 62%
“…Discourses that are more current include authors such as Letseka and Pitsoe (2014) and Cooper, Ralph and Harris (2017) who argue that academic knowledge is often organised around the dominant and prescriptive view of knowledge. This could lead to a mismatch between the RPL candidates' experiential knowledge and academic knowledge, or, on the other hand, the candidates' practice skills and expected professional skills.…”
Section: Recognition Of Prior Learning: a Contested Discourse And Pramentioning
confidence: 99%